Comparative Study of Governance Information Systems for Scientific Research - Benmoussa, Khaoula; Laaziri, Majida; Khoulji, Samira; Mohamed Larbi, Kerkeb (Transactions on Engineering and Computing Sciences, 2017)
The research and innovation effort is a major asset in international economic competition. Research and technological development are key areas to achieve this, contributing to economic growth and job creation. In order to achieve the objective of becoming the most competitive and dynamic knowledge-based economy in the world, several government have developed in recent years information systems to manage their scientific research. As part of the development of instruments to support the strategic management of research at an institution, in particular a university, the design of an information system that meets the requirements of a high level of operational, tactical and strategic institutional authorities seems paramount. International models of research governance or simply the remarks of faculty-researchers at universities help to build a performance management information system. In this article we will present a comparative study between the information systems of scientific research, in particular the Chile Research Management System (SGI) and the Argentine Science and Technology Information System (SICyTAR), Scientific Information System of Andalusia Spain (SICA), GRAAL of France (management of research data, application of laboratory activities) and others.